Psychological features of correlation between personal and religious orientations - Melnyk, Ylia (Psychological Prospects Journal, 2017)
In this article the issue of correlation between religious orientations and important personal formation and characteristics, related to comparison of oneself with other people has been investigated. The author relies on H. Allport’s well-known personal concept of external and internal religiosity and on basic principles humanistic psychological theory, that describes main components of personal self-actualization. The empirical method consists of «A measuring religious orientation» written by H. Allrort and D. Ross; and the «Self-actualization test (SAT)» («Personal Orientation Inventory» written be E. Shostrom and adapted by M. Kroz and L. Hozman). The sample is represented by 211 Ukrainian citizens: 109 full-time and part-time students (aged 17-30) and 102 employed and temporarily unemployed (aged 31-60). It is empirically determined that the representatives of the sample generally reach the criteria of personal maturity according to such criteria of self-actualization as «synergy», «the idea of ​​human nature» and «value orientations», otherwise, on the verge of norm and their lower indicators there are «spontaneity», «cognitive needs», «creativity» and «self-acceptance». According to the results of the study, statistically significant differences were noted in three areas. Between «weakly» and «externally» religiously oriented people - according to the scales of «representations about human nature» and «self-esteem» (significantly higher - respondents with a high external religious orientation). Then between «weakly» and «internally» religiously oriented individuals - according to the index of «scale of idea about the nature of man» (significantly higher - highly internally oriented respondents). And between «outsiders» and «internally» oriented individuals – according to the results of scales of «self-esteem» and «acceptance of aggression» (significantly higher - externally religiously-oriented respondents). The obtained data are interpreted as a substantially self-centered, personally self-tolerant basis of external religious orientation and a more sociocentric basis - internal orientation.